Court of the Moon, Golden Gate International Exposition, San Francisco (H.S. Crocker Co., Inc.)
The Court of the Moon and 400-foot Tower of the Sun at San Francisco's World's Fair on Treasure Island. "Black light" directed on fluorescent colored paints on the walls of exhibition palaces is one of many lighting innovations at this Fair.